2008
DOI: 10.1063/1.2975166
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dilute InAsN layers grown by liquid phase epitaxy

Abstract: We report on the liquid phase epitaxial growth of InAsN from indium rich solution. The spectral properties of dilute bulk alloys containing N∼0.5% and which exhibit photoluminescence in the midinfrared spectral range without any postgrowth annealing are described. The blueshift in the emission spectrum is attributed to a combination of tensile strain and band filling effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…These measurements showed that the low temperature ͑T = 4.2 K͒ PL emission red shifts from 0.42 eV to about 0.35 eV with increasing x from 0 to 1%, in qualitative agreement with optical data reported previously for InAs 1−x N x epilayers grown on other substrates ͑e.g., InP and InAs͒ or using different growth techniques. [11][12][13]15 A strong and broad PL emission centered at around 0.3 eV was also measured at room temperature ͑T = 300 K͒ in the InAs 1−x N x sample with x =1%. For further details on the PL properties of all samples, see Ref.…”
Section: Samples and Experimentsmentioning
confidence: 81%
See 1 more Smart Citation
“…These measurements showed that the low temperature ͑T = 4.2 K͒ PL emission red shifts from 0.42 eV to about 0.35 eV with increasing x from 0 to 1%, in qualitative agreement with optical data reported previously for InAs 1−x N x epilayers grown on other substrates ͑e.g., InP and InAs͒ or using different growth techniques. [11][12][13]15 A strong and broad PL emission centered at around 0.3 eV was also measured at room temperature ͑T = 300 K͒ in the InAs 1−x N x sample with x =1%. For further details on the PL properties of all samples, see Ref.…”
Section: Samples and Experimentsmentioning
confidence: 81%
“…Interest has focused more recently on narrow energy-gap semiconductors, such as InAs, which has a band gap E g = 0.35 eV at room temperature ͑T = 300 K͒. The incorporation of nitrogen in this compound induces large relative changes of E g , [10][11][12][13][14][15][16][17] thus, making the InAs 1−x N x alloy an attractive alternative to more established materials, such as Hg 1−y Cd y Te, for infrared ͑IR͒ gas sensing and security applications. InAs 1−x N x has proved to be a useful material for fabricating alloys with a photon absorption energy in the IR that can be tuned by the N concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we report on growth from solution using liquid phase epitaxy (LPE), which may offer an alternative route towards the production of high quality dilute nitrides provided that the N can be successfully incorporated. Previously, we have reported LPE growth of InAsN layers on InAs substrates where polycrystalline InN powder was added to the growth melt to supply N during growth [34]. In the present work we report on our attempts to improve on this by using GaN as a source of N instead of InN.…”
Section: Introductionmentioning
confidence: 95%
“…The two peaks located at 461 and 496 cm -1 we attribute to N-In 4 and N-Ga 2 In 2 clusters respectively [48]. The peaks at 413 and 487 cm -1 are related to higher order complexes and have been determined to be due to high order di-nitrogen In-N complexes [34] and doubly degenerate N-Ga 3 In cluster modes [48,49]. Finally, the peak located at 380 cm -1 is tentatively attributed to a gap mode caused by In vacancies [50].…”
mentioning
confidence: 99%
“…In particular, an increase in electron and hole effective masses enhances the joined densities of states and then reduces the injected carrier concentration required to reach laser operation in multiquantum well laser diodes. Consequently, several theoretical approaches have been developed to describe dilute-N InAsN electronic and optical properties [7][8][9], and InAsN layers grown on III-V substrates have been reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%